2012
DOI: 10.1074/jbc.m111.294801
|View full text |Cite
|
Sign up to set email alerts
|

A Screen for Enhancers of Clearance Identifies Huntingtin as a Heat Shock Protein 90 (Hsp90) Client Protein

Abstract: Background: Molecular chaperones assist in the folding of metastable proteins implicated in neurodegenerative diseases. Results: Huntingtin is a heat shock protein 90 (Hsp90) client protein. Conclusion:Hsp90 inhibition-mediated degradation of soluble mutant huntingtin is independent of a cellular heat shock response. Significance: Mechanisms targeting Hsp90 chaperone function may provide new treatments for Huntington disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
96
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 44 publications
4
96
0
Order By: Relevance
“…However, it is believed that the toxicity of A53T a-Syn is associated with formation of prefibrillar a-Syn oligomers (Kalia et al, 2013). Recent studies suggest that inhibition of Hsp90 could be beneficial for neurodegenerative diseases (McLean et al, 2004;Waza et al, 2005;Tokui et al, 2009;Baldo et al, 2012). Pharmacologic inhibition of Hsp90 has been shown to be useful in neurodegenerative disease models (Gallo, 2006;Luo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is believed that the toxicity of A53T a-Syn is associated with formation of prefibrillar a-Syn oligomers (Kalia et al, 2013). Recent studies suggest that inhibition of Hsp90 could be beneficial for neurodegenerative diseases (McLean et al, 2004;Waza et al, 2005;Tokui et al, 2009;Baldo et al, 2012). Pharmacologic inhibition of Hsp90 has been shown to be useful in neurodegenerative disease models (Gallo, 2006;Luo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the other major classes of HSPs, HSP90 preferentially interacts with a specific subset of proteins and is involved with maturation of signaling molecules including protein kinases, transcription factors, and hormone receptors (14,15). HSP90 possesses an intrinsic ATPase activity that is required for mediating the necessary conformational changes in client proteins for activation (15,17,18) and is also important for stabilization of the HSP90 client proteins (19,20). HSP90 inhibitors 17-allylamino-17-demethoxygeldanamycin (17-AAG) as well as other structurally distinct agents, including SNX-5422 (also known as PF-04929113) and NVP-AUY922, bind to the nucleotide binding pocket of HSP90 and inhibit the progression of the HSP90 complex toward the stabilizing form resulting in the degradation of the client proteins (16,19,(21)(22)(23).…”
mentioning
confidence: 99%
“…HSP90 possesses an intrinsic ATPase activity that is required for mediating the necessary conformational changes in client proteins for activation (15,17,18) and is also important for stabilization of the HSP90 client proteins (19,20). HSP90 inhibitors 17-allylamino-17-demethoxygeldanamycin (17-AAG) as well as other structurally distinct agents, including SNX-5422 (also known as PF-04929113) and NVP-AUY922, bind to the nucleotide binding pocket of HSP90 and inhibit the progression of the HSP90 complex toward the stabilizing form resulting in the degradation of the client proteins (16,19,(21)(22)(23). It is well established that pharmacological inhibition of HSP90 can lead to degradation of a large variety of client proteins including kinases such as RAF kinase, ERBB2, AKT, v-SRC, and death domain kinase, the transcription factors mutants p53 and HIF-1␣, the mineralocorticoid, glucocorticoid, and mutant androgen receptors, and others such as the cystic fibrosis transmembrane conductance regulator CFTR and huntingtin (19, 21, 24 -32).…”
mentioning
confidence: 99%
“…HSP90 inhibition is an attractive strategy to treat proteinopathies given its ability to stabilise client proteins, of which mHTT is one 75 . It was shown that the co-IP of HSP90 and mHTT is abrogated in the presence of HSP90 inhibitors and that mHTT is ubiquitinated and then degraded in a dose-dependent manner with HSP90 inhibitor.…”
Section: Therapeutic Approaches In Hd Targeting Chaperone Proteinsmentioning
confidence: 99%